It's already inside : nurturing your innate leadership for business and life success - Murray, Robert S. (Morgan James Publishing : Made available through hoopla, 2015)
If you thought that leadership-true, authentic values-based leadership-was all about mindlessly following directives from above and managing process, policy, and data, then you will be frustrated by your results, success, and happiness. Authentic leadership comes from inside-a place where logic meets emotion, where people connect with people, where character is contagious, strategy is simple, and people believe they are making a difference and are changing the world they live in. It's Already Inside is a leader's journey to unlock the secret to connecting emotionally with people, finding balance, and having a more successful and happy life by inspiring others to discover their remarkable potential. Each chapter features a story-based passage with thought-provoking questions to help you unlock your own authentic greatness. You'll finish It's Already Inside with more insight, focus, and results that will bring more success, better relationships, and happiness. Your trek through It's Already Inside will help you discover the leadership-nurturing lessons that come from author Robert Murray's: - Growing up with legendary athlete Terry Fox - Standing on the top of Mount Kilimanjaro - Accidently running one sunny summer morning with rock legend Billy Idol around a lake and learning what he had to say about life and business - Running from a grizzly bear - Having a friend die in his arms - Learning what aviators taught him about focus and getting things done - Being mistakenly arrested in the Hong Kong airport - Being "downgraded" by a major international airline And ... the most important life and leadership lesson Murray ever learned from his teenager.